Development and Characterization Studies on Bronze Alloy Surface Composites Through Friction Stir Processing - Cherian Paul, Mathew M D (International Journal of Advanced Science and Technology, 2020)
The investigation presents a comparative study on the microstructure, hardness and wear properties of bronze-tungsten carbide and bronze-alumina composites fabricated using the Friction Stir Processing (FSP) technique. Cu-10Sn bronze was used as the substrate while tungsten carbide (WC) and alumina (Al2O3) particulates with average grain size 10-20µ were used as the reinforcement. The reinforcements with varying %wt (5, 10 and 15) were used for developing the composite. The tin bronze alloy Cu-10Sn was prepared by sand casting and the cast samples were analyzed for chemical composition using arc spectrometry. The castings were then machined into bars of dimension 50x50x100 mm. The bars were then subjected to surface modification process using FSP. The ceramic particulates were applied on the surface of the substrate and the modification was carried out. The composites so produced were subjected to various tests, microstructure evaluation, SEM, hardness testing and wear testing respectively. Microstructural evaluation was carried out using inverted metallurgical microscope and the grain analysis was carried out using Metallurgical Image Analysis System (MIAS). Hardness testing was conducted using a micro-hardness tester (Make: Mitutoyo; Model: MVK – H11), with a load of 100 g-f applied for 15 sec. The wear testing was conducted in DUCOM Pin-On-Disc wear tester as per ASTM G99 under dry sliding conditions in air. The wear test parameters used were: load – 20 N, speed – 320 RPM, track diameter – 110 mm and sliding distance – 1800 m for a duration of 600s. A layered functionally graded bronze composite was developed using the Friction Stir Processing technique employed. The microstructural evaluation showed that the ceramic particulates were uniformly distributed in the modified layer formed as a result of FSP. It was also observed that the hardness as well as wear resistance improved with the addition of reinforcements. However, compared to alumina reinforced composites, WC reinforced composites exhibited superior hardness and wear resistance.